The Realization Concept. - Bierman, Jr., Harold; Black, Homer A.; Gray, Jack; Sapienza, Samuel R.; Davidson, Sidney (The Accounting Review, 1965)
This article focuses on the 1964 Concepts and Standards Research Study Committee of the American Accounting Association, which aimed to expand and to amend in part the statement on realization in "Accounting and Reporting Standards for Corporate Financial Statements–1957 Revision." That statement says the essential meaning of realization is that a change in an asset or liability has become sufficiently definite and objective to warrant recognition in the accounts. In considering this statement, and realization principles generally, attention will be focused on the problems of asset recognition and valuation and revenue recognition. The committee concurs with the statement of the 1957 Revision that primary emphasis should be given to the use by investors of published financial statements in making investment decisions and in exercising control over management. The committee recognizes the difficulty of developing a definition of realization that will have general applicability. Nevertheless, four of the committee members feel there is sufficient significance in the difference between realized and unrealized changes in value to justify making the distinction.